HISTOPATHOLOGICAL ANALYSIS OF DANEIO RERIO FED WITH ARTEMIA NAUPLII BIO ENRICHED WITH STREPTOMYCES COELICOLOR AP-09 SECONDARY METABOLITE - Hridhya KV; Srinivasan P; Rajalakshmi M; Dharshini K; Kavya R; Suresh S N; Bharathi V; Dhivya Dharshini S (The Bioscan, 2024)
Zebrafish (Danio rerio) is a small, tropical, bony fish that has a short lifespan and is very friendly to humans. These features make zebrafish an attractive and promising model organism for clinical trials because it is easy to use and inexpensive compared to other models. The digestive system, cardiovascular system, urinary system, nervous system and nervous system of zebrafish have similar characteristics to those of higher reproductive animals, and due to their diseases, adult zebrafish are used to detect environmental toxins and potential drug candidates through histopathological analysis. In this cases, the choice of the organ assessed relies on the type of compound tested, administration route, and biological activity. This study focused on the histopathological evaluation of the zebra fish exposed to experimental feeding trial of 14 days with A. nauplii biologically enriched with the crude secondary metabolite extracts of S. coelicolor AP09 strain. Fish were classified according to the percentage of bioaccumulated food obtained during the feeding experiment. This study focuses on evaluating the toxicity in the liver after treatment and the state of the immune system of fish after experimental feeding. By comparing the health status of the hepatocytes among the control and the test group it was identified that the test group zebra fishes (T1 to T3) that received different percentages bio enriched A. nauplii exhibited a near normal histological architecture as compared to the Control group.